2019
DOI: 10.1097/md.0000000000015852
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative combined administration of tranexamic acid and dexamethasone in total knee arthroplasty—benefit versus harm?

Abstract: Background: The purpose of this study was to investigate the benefits and harm of combined administration of tranexamic acid (TXA) and dexamethasone (Dexa) in total knee arthroplasty (TKA). Methods: A total of 88 consecutive patients undergoing TKA for knee osteoarthritis were stratified in 2 groups. All surgeries were performed under general anesthesia. Brief, patients in the TXA + Dexa group (n = 45) received 10 mg Dexa just after the anesthesia, and repeated at 24 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“… 11 Our results concur with most previous, but smaller, trials for the effect of high dose (>20 mg dexamethasone equivalent) glucocorticoid on morphine consumption and pain scores. 10 34 35 36 37 38 39 This DEX-2-TKA low risk of bias trial shows a statistically and patient important adjuvant analgesic effect of two doses of high dose dexamethasone, and with follow-up at 90 days.…”
Section: Discussionmentioning
confidence: 77%
“… 11 Our results concur with most previous, but smaller, trials for the effect of high dose (>20 mg dexamethasone equivalent) glucocorticoid on morphine consumption and pain scores. 10 34 35 36 37 38 39 This DEX-2-TKA low risk of bias trial shows a statistically and patient important adjuvant analgesic effect of two doses of high dose dexamethasone, and with follow-up at 90 days.…”
Section: Discussionmentioning
confidence: 77%
“…3,[12][13][14] Our results are in line with the results of other studies and meta-analyses. [1][2][3]6,[11][12][13][14][15][16][17][18][19][20] It is worth noting that the transfusion rates in the TXA group were even lower than in some of the previous reports. According to the meta-analysis by Kuo et al, in revision JRS, the transfusion rates can be as high as 15% with TXA and 38,7% in patients not receiving TXA.…”
Section: Discussionmentioning
confidence: 99%
“…Although these scores may be useful for identifying PONV risk, there remains a need to optimize strategies for decreasing such risk. At our institution, we implement an extensive ERAS protocol for risk reduction that includes, in addition to anesthesia precautions (ie avoiding volatile anesthetics 18 ), antiemetic prophylaxis, administration of IV dexamethasone, 19,20 a tranexamic acid bolus following induction, 21 substantial IV hydration, 22 and packing removal and nasogastric suctioning before extubation to minimize ingestion of blood. 13 In addition to these precautions, the post hoc analyses in our study identified 2 additional measures for potentially decreasing PONV risk: more aggressive antiemetic prophylaxis, and decreased reliance on postoperative opioids.…”
Section: Discussionmentioning
confidence: 99%